1999
DOI: 10.3386/w7326
|View full text |Cite
|
Sign up to set email alerts
|

The Economics of Residential Solid Waste Management

Abstract: This paper provides a broad overview of recent trends in solid waste and recycling, related public policy issues, and the economics literature devoted to these topics. Public attention to solid waste and recycling has increased dramatically over the past decade both in the United States and in Europe. In response, economists have developed models to help policy makers choose the efficient mix of policy levers to regulate solid waste and recycling activities. Economists have also employed different kinds of dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 53 publications
0
28
0
1
Order By: Relevance
“…In the economic literature the most prominent research has been done in two areas, pricing strategies and alternative waste disposal options (Hong and Adams, 1999;Kinnaman and Fullerton, 1999) and evaluating benefits of curbside recycling for households (Creel and Loomis, 1997;Huhtala, 1999;Caplan et al, 2002;Aadland and Caplan, 2003). Our study belongs to the second group, comparing benefits for households and costs of the NGP.…”
Section: Background Informationmentioning
confidence: 98%
“…In the economic literature the most prominent research has been done in two areas, pricing strategies and alternative waste disposal options (Hong and Adams, 1999;Kinnaman and Fullerton, 1999) and evaluating benefits of curbside recycling for households (Creel and Loomis, 1997;Huhtala, 1999;Caplan et al, 2002;Aadland and Caplan, 2003). Our study belongs to the second group, comparing benefits for households and costs of the NGP.…”
Section: Background Informationmentioning
confidence: 98%
“…Economists have generally focused research efforts in two areas: (1) feasibility and effectiveness of unit pricing strategies and/or alternative waste disposal options, such as recycling, in satisfying a community objective of reduced landfilling; and (2) measurements of household benefits of curbside recycling. Choe and Fraser (1998) or Kinnaman and Fullerton (1999) provide excellent overviews of this literature.…”
Section: Introductionmentioning
confidence: 99%
“…Properly planned and executed recycling programs have proven to be quite successful at reducing both waste and costs, and their effects on the environment (Hong and Adams, 1999;Koli and Mahamuni, 2005;Bhattarai, 2005;Kinnamann and Fullerton, 1999;Tanskanen, 2000). The LCI results showed that recycling is important because a long-term nationwide recycling effort extends and conserves scarce resources and ultimately reduces GHG emissions and GWP.…”
Section: Resultsmentioning
confidence: 90%